A Long and Winding Road from Narrator to Character: A Stylistic Analysis of Tom Robbins’ novel Fierce Invalids Home from Hot Climates - Blahút, Miloš (American & British Studies Annual, 2018)
Tom Robbins’ novel Fierce Invalids Home from Hot Climates (2000) provides a plethora of ways to obtain an insight into his characters’ minds and learn about their feelings and emotions by means of certain techniques of representing speech, thought, and perception, namely free indirect speech/thought, narrative report of thought act, and substitutionary perception/free indirect perception, to name but a few. The aim of this paper is to demarcate the boundaries between those modes of representation and through stylistic analysis to pinpoint examples of mode of representation which both reflect characters’ thoughts and perceptions, while at the same time reveal the narrator’s creativity while constructing the fictional world of the novel.